T cell-based strategies for HIV-1 vaccines - Bette Korber; Will Fischer (Taylor & Francis Group, 2020)
Despite 30 years of effort, we do not have an effective HIV-1 vaccine. Over the past decade, the HIV-1 vaccine field has shifted emphasis toward antibody-based vaccine strategies, following a lack of efficacy in CD8+ T-cell-based vaccine trials. Several lines of evidence, however, suggest that improved CD8+ T-cell-directed strategies could benefit an HIV-1 vaccine. First, T-cell responses often correlate with good outcomes in non-human primate (NHP) challenge models. Second, subgroup studies of two no-efficacy human clinical vaccine trials found associations between CD8+ T-cell responses and protective effects. Finally, improved strategies can increase the breadth and potency of CD8+ T-cell responses, direct them toward preferred epitopes (that are highly conserved and/or associated with viral control), or both. Optimized CD8+ T-cell vaccine strategies are promising in both prophylactic and therapeutic settings. This commentary briefly outlines some encouraging findings from T-cell vaccine studies, and then directly compares key features of some T-cell vaccine candidates currently in the clinical pipeline.